Device-assisted enteroscopy: With increasing requirements, national Irish data support a centralized high-volume model to achieve performance targets - Costigan, Conor; Connaughton, Roisin; Sihag, Sandeep; Leung, Edric; Butler, Thomas; O'Hara, Fintan John; Hall, Barry; McNamara, Deirdre (Endoscopy International Open, 2026)
Device-assisted enteroscopy (DAE) has seen a rapid increase in demand in recent years. European Society of Gastrointestinal Endoscopy (ESGE) DAE key performance indicators (KPIs) have been published as well as some national datasets. Data suggest variation in practice and service provision impacts outcomes. The aim of this study was to review DAE services in Ireland according to ESGE KPIs and wider outcomes.DAE data from records at Tallaght and Connolly Hospital from January 2015 to May 2024 were retrospectively collated.Overall, 941 studies were included. 798 (85%) were index procedures and 548 (58%) were on men with a mean age of 61. Double-balloon enteroscopy was used in 864 (92%), 745 (79%) were anterograde (ADBE), and 196 (21%) were retrograde (RDBE). Mean depths of insertion were 201 cm ± 101 cm for ADBE and 101 cm ± 67 cm for RDBE. Of the procedures, 868 (92%) used conscious sedation; median doses of midazolam and fentanyl were 5 mg and 75 µg, respectively, with a mean comfort score (Modified Gloucester Scale) of 1.45 ± 0.67. Overall yield was 63%. Therapeutic intervention was performed in 385 (41%), 98% successfully, whereas 91% of detected lesions were tattooed. Significant adverse events occurred in < 1%. ESGE major KPIs by intention to treat (result/target) were: approved indication (94%/95%), depth-of-insertion tattoo (64%/80%), lesion detection (59%/50%-70%), lesion marking (91%/95%), complications (3.3%/< 5%), and adequate comfort (98%/> 90%). All minor KPIs were met. KPIs were consistent between both high-volume Irish-centers and were comparable to the three high-volume UK centers published in the recent DEEP-UK study, all of which performed better than lower-volume UK centers. Conscious sedation was used predominantly in our cohort with acceptable outcomes.DAE requirement is increasing. Our study suggests that a high-volume model ensures compliance with international KPIs. These data also suggest that conscious sedation is a viable option for the majority of DAEs without reducing effectiveness, while maintaining comfort.
Keywords: Endoscopy Small Bowel; Capsule endoscopy; Small intestinal bleeding; Inflammatory bowel disease